Efektivitas dan Koordinasi Multi-Aktor dalam Penanggulangan Bencana di Sumatera Barat - Rindu Wahyuni; Syalfa Rahmadani; Boni Saputra (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
West Sumatra is one of the regions in Indonesia with a high level of disaster vulnerability based on data from the 2024 Indonesian Disaster Risk Index (IRBI). Its geographical location within the Ring of Fire makes it vulnerable to earthquakes, tsunamis, floods, landslides, and flash floods of cold lava flows. The high intensity of disasters demands effective, integrated, and responsive disaster management. However, the implementation of disaster management policies in West Sumatra still faces obstacles, such as sectoral egos between agencies, weak integration of disaster information, limited resources, and suboptimal cross-sectoral coordination at every stage of the disaster. These conditions have resulted in suboptimal mitigation, preparedness, emergency response, and post-disaster rehabilitation processes. This article aims to analyze the effectiveness and multi-actor coordination in disaster management in West Sumatra through a collaborative governance perspective. The research uses a literature review method with a descriptive and thematic analysis approach to scientific journals, books, policy documents, and regulations related to disaster governance. The analysis was conducted by identifying the relationship between policy effectiveness, inter-institutional communication, community participation, and the quality of collaboration within the disaster management system. The study results indicate that disaster management effectiveness is influenced by the quality of inter-institutional coordination, policy communication, clarity of role allocation, and community participation. A collaborative governance approach through the Pentahelix model and the Disaster Risk Reduction Forum (FPRB) can strengthen synergy between actors and increase community resilience to disaster risks. Furthermore, strengthening coordination forums is necessary to improve the effectiveness of regional disaster management policies.